Making of home: Transportation mobility and well-being among Tucson refugees. (July 2022) - Smith, Chandler; Myadar, Orhon; Iroz-Elardo, Nicole; Ingram, Maia; Adkins, Arlie
Abstract: The article is based on a multidisciplinary research project that aimed to study mobility challenges that refugees in Tucson, Arizona experience after their resettlement. Using qualitative and quantitative data collected from interviews and survey data, we argue that mobility shapes the ways refugees foster social connections, attain employment and access educational opportunities. Accordingly, barriers to mobility negatively impact refugees' perception of well-being in post resettlement. However, these challenges are not experienced unevenly. Nor are refugees passive subjects who lack agency in overcoming various barriers they experience. The study also reveals the resilience of the refugee community in navigating the intersectional challenges they confront related to their mobility. We hope that the implications of this study can inform various stakeholders to better support refugees in navigating existing mobility and transportation challenges and to promote policy change that can increase better spatial mobility for all Tucson community members.